DC and AC Circuit Parameters of Hybrid InAs/GaAs and GaSb/GaAs Quantum-Dot Solar Cells - Prasatsap, Unchittha; Kiravittaya, Suwit; Thainoi, Supachok; Panyakeow, Somsak (Asian Health, Science and Technology Reports, 2020)
We investigate DC and AC circuit parameters of hybrid quantum-dot (QD) solar cells consisted of self-assembled InAs/GaAs and GaSb/GaAs QDs. The hybrid QD solar cell samples are fabricated by stacking of one pair and three pairs of InAs/GaAs and GaSb/GaAs QD layers in molecular beam epitaxy. A measurement circuit has been used for both DC and AC parameter extraction. Numerical values of the parameters are extracted from the fittings of experimentally measured current-voltage characteristics and frequency responses of the samples under controlled bias condition. The fitting functions are derived from the considered equivalent circuit models. Extracted series and shunt resistance values can be related to the sample structure. For the AC characteristics, a low shunt resistance and a high capacitance of three-pair hybrid QD solar cell are observed. We attribute the latter to the high number density of buried QDs in the sample. These findings shed light on the relationship between electrical characteristic of QD devices and their structure.